Cytological, Histopathological and Haematological Evaluation of Canine Mammary Tumours: A Comparative Study with Human Breast Cancer - Narad, Ankur; Shukla, Supriya; Prasad Jatav, Gaya; Kashiram Jayraw, Anantrao; Prakash Shukla, Brahma (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine tumours, particularly mammary gland tumours, are among the most common neoplastic conditions in dogs, paralleling the frequency and complexity of human breast cancer. This study was designed to evaluate canine tumours through cytological, histopathological, and haematological techniques, while also drawing a comparative analysis with human breast cancer. Tumour samples were collected from 30 clinical canine cases and evaluated using Fine Needle Aspiration Cytology (FNAC) and histopathology to classify the types of tumours and identify malignancies. Additionally, haematological parameters such as total leukocyte count and differential leukocyte count were analyzed to assess systemic changes in the affected dogs. In parallel, 30 human breast cancer tissue samples, classified according to the WHO guidelines, were studied to highlight similarities and differences between canine and human mammary tumours. The results revealed key cytological and histopathological features that align with human breast cancer types, particularly in invasive forms. Haematological findings in dogs indicated significant alterations, mirroring some patterns observed in human cancer patients. This comparative approach provides insights into the biological behaviour of canine tumours and their relevance as a model for human cancer studies, potentially aiding in the development of more effective diagnostic and treatment strategies for both species. These findings underscore the importance of cross-species oncology research and suggest that further comparative studies could enhance our understanding of tumour pathogenesis and therapeutic approaches in both veterinary and human medicine.